Staying Employed and Employing Others: Leadership Styles and Management Strategies of Proprietors of Micro Enterprises in Developing Countries - Akpamah, Peter (International Journal of Engineering and Management Sciences, 2019)
This study sought to find out the leadership style and management strategies of the proprietors of micro enterprises that have enabled them to stay in business this long and offering employment to several others in the midst of unfavourable economic conditions in developing countries. Management strategy and leadership style are complementary in pursuing organizational goal. Though, literature on the subject reveals that not much research has been done on the survival of micro business on the African’s continent regarding owners’ management strategies and the leadership style. We used mix methods in data collection and purposive samplings of thirty (30) micro enterprises’ proprietors were interviewed. The result reveals that owners of micro business practice multistrategies in their organizations. The Study found out that the Laissez Faire or Free Rein Leadership and the Bureaucratic Leadership were not practiced by any of the research participants. However, Authoritarian Leadership with strict instructions dominated Democratic Leadership and appeared to have been very effective and yielded result in most micro businesses.